Silicon nitride Mach-Zehnder interferometer for on-chip quantum random number generation. (December 2020) - Prokhodtsov, A; Kovalyuk, V; An, P; Golikov, A; Shakhovoy, R; Sharoglazova, V; Udaltsov, A; Kurochkin, Y; Goltsman, G
Abstract: In this work, we experimentally studied silicon nitride Mach-Zehnder interferometer (MZI) with two directional couplers and 400 ps optical delay line for telecom wavelength 1550 nm. We achieved the extinction ratio in a range of 0.76-13.86 dB and system coupling losses of 28-44 dB, depending on the parameters of directional couplers. The developed interferometer is promising for the use in a compact random number generator for the needs of a fully integrated quantum cryptography system, where compact design, as well as high generation speed, are needed.